Evaluation of bone marrow lesions as a manifestation of subchondral bone disease - Stewart, Holly Lynn, author; Kawcak, Christopher E., advisor; Easley, Jeremiah T., committee member; Puttlitz, Christian M., committee member; Selberg, Kurt T., committee member (Colorado State University. Libraries, 2021)
To view the abstract, please see the full text of the document.
Keywords: osteoarthritis; BMLs; animal models; subchondral bone; articular cartilage; joint function; cellular; molecular; immunologic; lesions; CT; MRI